Becoming Indonesia: Political Gait of the Arabs in the Pre-Independence Period - Abdul Wahid Hasyim (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This article addresses the political gait of the Arabs in Pre-Independence Indonesia. Using a qualitative method with a historical approach, this article aims to parse the political role of Arabs in Indonesia, the achievements they have, and the challenges they have faced since they first came to Indonesia until the country became independent in 1945. This study identifies several things. First, the involvement of Arabs in Indonesian politics has been going on since the time of the kingdom or empire. Some Sayyids are believed to occupy important positions, such as advisors to the king, foreign diplomats, and ministers. Second, in modern times, primarily until 1945, Arabs, both individually and in groups, have played an essential role in the constellation of Indonesian politics. In addition to establishing and developing PAI (called the Indonesian Arab Association initially but changed to the Indonesian Arab Party) in 1934, its figures, especially A.R. Baswedan and Hamid Algadri, were among the prominent figures during the Indonesian independence process. Third, there was a change in tendency in which the Arabs no longer struggled with aspects of the trade, as their initial motivation to emigrate to the archipelago, but began to be involved in various spheres of Indonesian people's lives, including in state politics. They have become essential figures of Indonesian society. With the political role played, they gain a stronger identity, increasingly 'becoming Indonesia'.